Percutaneous Foraminal Neuroplasty Using Reference Spinal Needles: Technical Description - Victor M. Silva-Ortiz; Alaa Abd-Elsayed; Jesus Medina-Razcon; Christopher L. Robinson (Pain and Therapy, 2024)
Abstract Background Lumbar foraminal stenosis is a common cause of chronic lower back pain and radiculopathy often treated by epidural steroid injections. In the absence of imaging findings with a positive physical exam demonstrating symptoms, percutaneous neuroplasty (PNP) may be an alternative to transforaminal epidural steroid injections that have otherwise failed. Case Presentation We present two cases (55-year-old man and 65-year-old woman) with chronic low back pain and radiculopathy with otherwise normal imaging demonstrating no lumbar foraminal stenosis refractory to transforaminal epidural steroid injections. PNP was performed using reference spinal needles with both patients achieving sustained > 50–75% pain relief. Conclusion PNP offers interventional chronic pain physicians and patients with refractory chronic low back pain with lumbar radiculopathy due to fibrosis an alternative, safe treatment that offers sustained results. Furthermore, this is the first of its kind to offer a step-by-step procedural step of PNP using a reference spinal needle.